Analysis of Petty Cash Effectiveness to Improve the Quality of Cash Control System at PT. Inifd Kreasi Indonesia - -, Indah Permata Sari; Tantri, Sakina Nusarifa (CONSISTENCY: Journal of Communication and Information in Accountancy, 2025)
Purpose – PT Inifd Kreasi Indonesia main business is on fashion and interior design school. They are the first franchisee in Indonesia, with office on Gunung Sahari St, Central Jakarta. This research aim to analyze the benefit of petty cash for cash management operation on PT Inifd Kreasi Indonesia. Design/methodology/approach – This research using mainly qualitative method through observation and documentation of interview. In the end, we could imply that PT Inifd Kreasi Indonesia itself using imprest fund method, by limiting the fund of petty cash each period according to company policy. Findings – It is expected that this research could comprehend the whole process of allocation and bookkeeping of petty cash for detection of fraud and unecessary expenses. This found that the implementation of petty cash can improve the cash control system at PT Inifd Kreasi Indonesia.